Contributing Factors to Science Achievement in TIMSS Malaysia: Direct Model and Indirect Model - Ismail, Mohd Erfy; Samsudin, Mohd Ali; Amin, Nor Fadila Mohd; Kamarudin, Nurzatulshima; Daud, Khairul Azhar Mat; Halim, Lilia (International Journal of Engineering and Technology, 2018)
The purpose of this study is to examine the extent to which home context, classroom context and school context influence students' science achievement in Trends in International Mathematics and Science Study (TIMSS) 2011. This study involved a total of 5733 respondents from 180 secondary schools in Malaysia based on TIMSS 2011 data. Random sampling using two stage stratified cluster sampling technique was done in selecting the sample. This study also proposes a model containing two exogenous constructs which are parental involvement and school discipline as well as two endogenous constructs which are attitudes towards science and science achievement. This study used structural equation modeling (SEM) technique to test the direct model, indirect model and to determine the strength of the relationship between one variable with another variable. The findings showed that parental involvement has a direct effect on students' attitudes toward science and students' science achievement while the student attitudes towards science have a negative relationship towards students' science achievement.